Intuitionistic fuzzy neural network for time series forecasting - The case of metal prices - Hájek, Petr; Olej, Vladimír; Froelich, Wojciech; Novotný, Josef (Springer Nature Switzerland AG, 2021)
Forecasting time series is an important problem addressed for years. Despite that, it still raises an active interest of researchers. The main issue related to that problem is the inherent uncertainty in data which is hard to be represented in the form of a forecasting model. To solve that issue, a fuzzy model of time series was proposed. Recent developments of that model extend the level of uncertainty involved in data using intuitionistic fuzzy sets. It is, however, worth noting that additional fuzziness exhibits nonlinear behavior. To cope with that issue, we propose a time series model that represents both high uncertainty and non-linearity involved in the data. Specifically, we propose a forecasting model integrating intuitionistic fuzzy sets with neural networks for predicting metal prices. We validate our approach using five financial multivariate time series. The results are compared with those produced by state-of-the-art fuzzy time series models. Thus, we provide solid evidence of high effectiveness of our approach for both one- and five-day-ahead forecasting horizons.
Intuicionistická fuzzy neuronová síť pro predikci časových řad - případ cen kovů
Keywords: fuzzy neural network; fuzzy time series; intuitionistic fuzzy sets